Application of Resident Administration Services in The City of Paringin Web-Based - Audia, Rini; Sugiantoro, Bambang (Proceeding International Conference on Science and Engineering, 2020)
Paringin District have an application that is still in manual form and not computerized, and searching for information is still lacking because there is on online system so it is easy for citizents to access. So it is slow in the process of adding, changing and deleting data, and seeking information, as well as other population data collection. The purpose of making an administrative service application at this eligible village office so that it can help provide alternative problem solving such as data collection the number of people who come, move, die and are born. It’s easy to get correspondence if needed quickly, get complete information for residents, safe in data storage in the long run and the data is neatly arrange in the application. The method in this study by utilizing certain techniques is with field studies and literature studies. The result of this study are a set of administrative service application software in the Layap village office of Paringin subdistrict. The conclusion of this study is that in the application design provides a lot of convenience in the data processing process in the village office.